Penerapan Digital Marketing pada UMKM Batik Sembung di Kulonprogo - Kartika Wati, Setiani; Fadhilah,, Muinah; Widodo, Erry Kurniawati (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the application of digital marketing to Batik Sembung SMEs in Kulon Progo in a review of strategic marketing management. This study used a qualitative descriptive analysis method with the object under study was the UMKM Batik Sembung in Kulon Progo, Yogyakarta. The results show that Batik Sembung has used social media to inform and communicate with consumers. Social media that is often used is Facebook, Instagram, Youtube, Tiktok and Whatsaap. The platform is quite effective in informing Batik Sembung products and interacting directly with consumers. The obstacles faced by Batik Sembung in implementing digital marketing are unstable internet connections, delays in delivery, and the difficulty of educating the public to distinguish between written, stamped and printed batik through photos displayed in online sales. The application of digital marketing through social media makes it very easy for consumers to shop anywhere, anytime and is proven to be able to be used as a medium to increase sales. Keywords: Batik Sembung, digital marketing, social media.